Economic production quantity model involving repair, waste disposal, electricity tariff, and emissions tax - Utama, Dana Marsetiya; Lubis, Imtiaz Habib (Universitas Serang Raya, 2024)
This research aims to develop a new model for a comprehensive Economic Production Quantity (EPQ) by considering repair processes, waste disposal, electricity tariffs, and emission taxes to optimize inventory management decisions in two shops. The first shop is responsible for providing new manufacturing and remanufacturing products required by the second shop, which focuses on inventorying finished products to meet demand. The main objective of the proposed Model is to minimize total cost. The Model is formulated as Integer Non-Linear Programming (INLP) to represent the complexity of production and inventory decisions. This study applies a Genetic Algorithm (GA) approach run using Microsoft Excel software with the Solver feature To optimize the solution of the proposed Model. Sensitivity analysis shows that while increases in electricity tariffs and emissions taxes significantly increase the total costs incurred by firms, these factors do not directly reduce total energy consumption or carbon emissions. Instead, increased costs generally result in smaller optimal production batch sizes, which does not necessarily translate into reduced energy use, as operational energy requirements remain constant. Our findings emphasize the delicate balance between cost components and energy use, highlighting that increased electricity costs and emissions do not directly lead to overall cost savings or improved energy efficiency.